Intensification of Asian dust storms during the Mid-Pliocene Warm Period (3.25-2.96 Ma) documented in a sediment core from the South China Sea - Süfke, Finn; Kaboth-Bahr, Stefanie; Wei, Kuo-Yen; Chuang, Chih-Kai; Gutjahr, Marcus; Pross, Jörg; Friedrich, Oliver (Quaternary science reviews, 2022)
Dust storms are an important component of the global climate system. At the same time, they also bear a risk for human health by causing pulmonary diseases. Today, East Asian dust storms account for as much as half of the global dust emissions and temporarily affect highly populated areas. Therefore, understanding their mechanisms and predicting their evolution under warmer near-future climate conditions is of major interest. The mid-Pliocene Warm Period (mPWP; 3.264-3.025 Ma) is considered one of the best analogues from the past for anthropogenic climate change. Consequently, understanding the climate dynamics and associated environmental change during the mPWP can help with predicting the environmental effects of warmer-than-present climates. In order to reconstruct Asian dust storm evolution during the mPWP we have analyzed a sediment core from the northern South China Sea (SCS) for its elemental composition, grain-size variations and radiogenic isotope signature for the interval spanning from 3.69 to 2.96 Ma. We show that shortly after the first strong northern hemisphere glaciation (Marine Isotope Stage [MIS] M2; 3.25 Ma) atmospherically transported dust appeared in the northern SCS and this dust deposition prevailed throughout the mPWP. Atmospheric dust input further intensified with the onset of the MIS KM2 glaciation at 3.15 Ma, with distinct and strong dust storms occurring periodically from that time onwards. The increase in atmospherically transported dust can be attributed to the cooling and drying of interior Asia over the course of the mPWP along with an intensification of the East Asian Winter Monsoon and a potential southward shift of the westerlies.
Gesehen am 26.09.2022